FOREIGN LANGUAGE EDUCATION AS A PHILOSOPHICAL, SOCIAL, PSYCHOLOGICAL AND PEDAGOGICAL CATEGORY - Onishchuk, Irina (The Modern Higher Education Review, 2018)
Foreign language education is one of the priority areas of Ukraine's educational policy. It exists not only for teaching students to acquire a foreign language, but also aims to enrich the inner world of a person, to make it more erudite, bring society to a new level. One of the strategic directions in modernizing of education is the overcoming of reproductive mass education and the transition to a new educational paradigm, which provides cognitive activity and autonomy of thinking of those who study. "The school should teach how to think and teach how to study» - these are the pedagogical imperatives of the modern era.